Learning Management of Student Center Based Physical Education in Improving Student Character - Arnaz Anggoro Saputro (Universitas Majalengka, 2023)
Learning management is an important thing that needs attention, in this case an understanding of the 2013 curriculum needs to be mastered by a teacher so that learning is effective. The lack of teacher facilities or media to add insight into this matter is the impact of inappropriate learning. Based on this, it is necessary to know how to manage physical education learning at SMP Negeri 1 Jombang. Descriptive qualitative methods are used to find out findings in the field and these analytical methods can present research results in more detail. 2 teachers who teach physical education were selected as research respondents based on the criteria of the subjects taught. Data collection uses the help of observation guide instruments, interviews and documentation. Through the research that has been done, it was found that the management of physical education at SMP Negeri 1 Jombang has been carried out well. However, there are several factors that need to be improved, namely regarding the preparation of teachers in completing learning equipment such as syllabus before learning activities are carried out. The lesson plan is prepared so as not to create the impression that a sports and health physical education teacher is carrying out his duties. their daily life only carries out their obligations or only fulfills the demands of their superiors which in the end student learning outcomes become less than optimal.